From Slavery to Uncertain Freedom : The Freedman's Bureau in Arkansas 1865-1869 - Finley, Randy, 1954- (Book collections on Project MUSE., 1996)
As black Arkansans emerged from chattel slavery in the aftermath of the Civil War and the Emancipation Proclamation, they were supported in their efforts to redefine their lives by the work of the Freedmen's Bureau, a federal agency monitoring the South to ensure that at least a modicum of freedom was granted to the new citizens. In this account of the gains made by Arkansas freedmen during this period, Randy Finley takes a fresh approach by telling the story from the perspective of the blacks and whites who directly benefited from the Bureau, rather than from the perspective of the government bureaucrats, as found in reports from other states. Freedpersons tested their freedom in many ways - by assuming new names, searching for lost family members, moving to new residences, working to provide for their families, learning to read and write, forming and attending their own churches, creating thier own histories and myths, struggling to obtain land, and establishing different, nuances in race, gender, and class. As they built a bridge from slavery into freedom in these early years, African Americans learned for themselves that genuine psychological freedom is not granted by others.